1999
DOI: 10.1095/biolreprod60.4.996
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cloned Calves Following Nuclear Transfer with Cultured Adult Mural Granulosa Cells1

Abstract: Adult somatic cell nuclear transfer was used to determine the totipotent potential of cultured mural granulosa cells, obtained from a Friesian dairy cow of high genetic merit. Nuclei were exposed to oocyte cytoplasm for prolonged periods by electrically fusing quiescent cultured cells to enucleated metaphase II cytoplasts 4-6 h before activation (fusion before activation [FBA] treatment). Additionally, some first-generation morulae were recloned by fusing blastomeres to S-phase cytoplasts. A significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
465
8
22

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 665 publications
(514 citation statements)
references
References 48 publications
19
465
8
22
Order By: Relevance
“…2 Departamento de Medicina Veterinária Preventiva e Reprodução Animal, FCAV -UNESP, Via de Acesso Prof. Paulo Donato Castellane, s/n, 14884-900, Jaboticabal, SP, Brazil. 3 Departamento de Ciências Básicas, FZEA -USP, Avenida Duque de Caxias Norte, 225, 13635-900, Pirassununga, SP, Brazil. somatic cell nuclear transfer (SCNT; Wells et al, 1999), intracytoplasmic sperm injection (ICSI; Suttner et al, 2000) and round-spermatid injection (ROSI; Loren & Lacham-Kaplan, 2006). Furthermore, activation is used for elucidation of events during early embryonic development (Soloy et al, 1997) and for studies on genomic imprinting (Solter, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…2 Departamento de Medicina Veterinária Preventiva e Reprodução Animal, FCAV -UNESP, Via de Acesso Prof. Paulo Donato Castellane, s/n, 14884-900, Jaboticabal, SP, Brazil. 3 Departamento de Ciências Básicas, FZEA -USP, Avenida Duque de Caxias Norte, 225, 13635-900, Pirassununga, SP, Brazil. somatic cell nuclear transfer (SCNT; Wells et al, 1999), intracytoplasmic sperm injection (ICSI; Suttner et al, 2000) and round-spermatid injection (ROSI; Loren & Lacham-Kaplan, 2006). Furthermore, activation is used for elucidation of events during early embryonic development (Soloy et al, 1997) and for studies on genomic imprinting (Solter, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that a small proportion of ovarian GCs that are isolated from antral follicles can divide and form colonies, which demonstrates that some GCs exhibit the growth characteristics of stem cells [23][24][25][26][27]. Furthermore, prior studies have indicated that the success rate of cloning by nuclear transfer from GCs was 2.8% [28], compared with overall success rates of less than 0.4% from mammary epithelial cell lines [29] and 0.9% from cumulus cells [30], respectively. Do GCs possess TA because they originate from stem cells, and what is the level of TA exhibited in GCs during various stages of follicular development?…”
Section: Levels Of Ta In Luteinised Gcsmentioning
confidence: 99%
“…63(9): 945-948, 2001 Production of cloned animal by somatic cell nuclear transfer has recently been developed. The birth of live offspring derived from embryos reconstructed with somatic cells have been reported in several species; sheep [10], cattle [1,3,8], and mouse [7].Animal cloning technology can be used to preserve endangered mammalian species by interbreed or interspecies nuclear transfer. The success of interbreed nuclear transfer was reported in last surviving cow of the Enderby island cattle breed [9].…”
mentioning
confidence: 99%
“…63(9): 945-948, 2001 Production of cloned animal by somatic cell nuclear transfer has recently been developed. The birth of live offspring derived from embryos reconstructed with somatic cells have been reported in several species; sheep [10], cattle [1,3,8], and mouse [7].…”
mentioning
confidence: 99%